Perkembangan Startup Digital di Indonesia: Sebuah Tinjauan - Judijanto, Loso (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The rapid growth of digital startups in Indonesia has transformed the country into a dynamic hub for technological innovation and entrepreneurship in Southeast Asia. This research paper explores the multifaceted development of digital startups in Indonesia, examining the factors that have contributed to their growth, the challenges they face, and the opportunities that lie ahead. Through a comprehensive literature review, this study investigates the role of government policies, private sector investment, and community initiatives in fostering a thriving startup ecosystem. It also analyzes the impact of digital startups on various sectors such as e-commerce, fintech, edutech, and healthtech, highlighting their contribution to economic growth and social development. Furthermore, this paper identifies key challenges faced by startups, including regulatory hurdles, skill gaps, and access to funding, while also emphasizing the vast opportunities presented by Indonesia's large population, increasing internet penetration, and supportive ecosystem. By providing a comprehensive overview of the digital startup landscape in Indonesia, this research contributes to a deeper understanding of the factors driving their success and the challenges they must overcome to achieve sustainable growth